2015
DOI: 10.12659/msm.894484
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Cubic Liquid Crystalline Nanoparticles for Transdermal Delivery of Paeonol

Abstract: BackgroundThe aim of this study was to optimize the preparation method for self-assembled glyceryl monoolein-based cubosomes containing paeonol and to characterize the properties of this transdermal delivery system to improve the drug penetration ability in the skin.Material/MethodsIn this study, the cubic liquid crystalline nanoparticles loaded with paeonol were prepared by fragmentation of glyceryl monoolein (GMO)/poloxamer 407 bulk cubic gel by high-pressure homogenization. We evaluated the Zeta potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The polarization phenomenon was investigated using PLM. The observation was recorded, and the drawing of the sample was conducted at room temperature [ 31 ] .…”
Section: Methodsmentioning
confidence: 99%
“…The polarization phenomenon was investigated using PLM. The observation was recorded, and the drawing of the sample was conducted at room temperature [ 31 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous amphiphilic molecules gain the ability to form lyotropic liquid crystals in water via self-assembly. Examples include phytantriol (PT), 37,61 glyceryl monooleate (monoolein, GMO or MO), 62,63 glyceryl monolinoleate (monolinolein, GML or MLO), 64,65 oleyl glyceryl (OG) 66 and phytanyl glycerate (PG), 67 and other lipids such as phospholipids, 68,69 phosphatidylethanolamine, [70][71][72] glycolipides, 73 and alkyl glycerates. 74 Nevertheless, the phase behavior of different amphiphilic molecules is not the same, which can be ascribed to the difference in the hydrophilic hydration intensity, the number of alkyl chains, length and the degree of unsaturation Ben J. Boyd et al 35 suggested the fact that OG and PG were able to form the reversed hexagonal phase in excess water at the physiological temperature.…”
Section: Prescription Factorsmentioning
confidence: 99%
“…The use of PLA biodegradable material can overcome the shortcomings of low drug utilization, poor safety, short-term effects, high doses, and blood drug concentration fluctuations caused by frequent use and can reduce the side effects of the target drug. Moreover, PLA NPs have attracted considerable attention owing to good surface modification, targeting ability, stability, sustained release, and simple and convenient preparation [54,55]. Thus, with a small size, high loading capacity, and simple operation, the DG-PLA-NPs have promising prospects in practical applications.…”
Section: Discussionmentioning
confidence: 99%